Basics of Elbow Arthroscopy - Melissa L. Carpenter, B.S.; Jose F. Vega, M.D.; Monique Haynes, M.D.; Zeeshan A. Khan, B.A.; Juan Bernardo Villarreal-Espinosa, M.D.; Michael J. Murray, B.S.; Nikhil N. Verma, M.D. (Arthroscopy Techniques, 2025)
Elbow arthroscopy can be utilized to treat a variety of elbow pathologies. With recent advancements in arthroscopic technology and our understanding of elbow anatomy, several approaches to elbow arthroscopy have been proposed. However, a “gold-standard” has yet to be defined. In this Technical Note, the authors describe a systematic approach to perform elbow arthroscopy in the lateral decubitus position. Strategic placement of portals reduces the risk of damage to neurovascular structures. Our surgical technique aims to offer a safe, reproducible method for achieving excellent visualization and access to both anterior and posterior compartments, thereby optimizing outcomes and minimizing complications.